Sulfonated Mesua ferrea Linn Seed Shell Catalyzed Biodiesel Synthesis From Castor Oil – Response Surface Optimization - Karmakar, Bisheswar; Ghosh, Bidipta; Halder, Gopinath (Frontiers in Energy Research, 2020)
Biodiesel has been adopted in various countries as an alternative to petro-fuels and has been able to cater to transport sector requirements. A wide range of feedstock can be used for many production approaches, some of which are not cost-effective and are obsolete. Since waste biomass usage is an effective approach for resource recirculation, and edible oils cannot be used as feedstock to avoid straining food resources, the current investigation presents the optimization of biodiesel from raw castor oil using carbonized Mesua ferrea linn (MFL) seed shells as a heterogeneous catalyst after steam activation and H2SO4 doping. Proximate analysis of the oil showed high free fatty acid (FFA) content, which meant that acid catalyst was necessary for fuel production. Characterization of the inert char and acid catalyst showed good physical activation and effective doping. A 4-factor central composite design (CCD) experimental matrix was used for optimizing the acid esterification using methanol. Under optimal conditions, an actual yield of 92% as opposed to 86% predicted yield was observed at 60°C when run for 1.5 h with 7% catalyst under 950 rpm at 70% w/w alcohol concentration. Fuel characterization showed that fuel-grade RCME (Ricinus communis methyl esters) has physico-chemical properties within acceptable ASTM limits for biodiesel. gas chromatography analysis of fuel showed that acid esterification was able to convert the FFAs into methyl esters. The process adopted can thus provide a good way of turning waste biomass into an effective catalyst capable of converting non-edible feedstock like castor oil into biodiesel.